Pengalaman Mahasiswa Universitas PGRI Semarang dalam Menikmati Es Kopi Kekinian - Wildan Alfarizi; Arif Dwi Kurniawan; Rauly Sijabat (INDO PUBLISHING, 2026)
This study, using a qualitative approach, aims to explore in-depth the subjective experiences of students at Universitas PGRI Semarang when enjoying contemporary iced coffee, including their feelings, perceptions, meanings, and emotional experiences. Phenomenology is used to understand the essence of a person's life experiences through direct descriptions of their experiences. Data collection techniques were conducted using in-depth interviews. Based on the research results and discussion regarding the experiences of Universitas PGRI Semarang students in enjoying contemporary iced coffee, it can be concluded that the activity of drinking coffee has a broader meaning than simply consuming the beverage. Students' experiences of enjoying contemporary iced coffee are shaped by three main aspects: sensory, emotional, and social experiences. From a sensory perspective, students consider the taste, aroma, and quality of the coffee as important factors in determining satisfaction. From an emotional perspective, contemporary iced coffee provides a sense of comfort and relaxation, and helps reduce stress caused by academic pressure. Meanwhile, from a social perspective, drinking coffee serves as a means to socialize, discuss, and strengthen friendships. Furthermore, social media plays a role in introducing new trends and coffee shops, although students still consider comfort and personal preferences in making their choices. Overall, contemporary iced coffee is interpreted as part of the UPGRIS student lifestyle, linked to self-identity, comfort, and togetherness. Keywords: Drinking Coffee; Students ABSTRAK Penelitian ini menggunakan pendekatan kualitatif penelitian ini bertujuan untuk menggali secara mendalam pengalaman subjektif mahasiswa di Universitas PGRI Semarang ketika menikmati es kopi kekinian meliputi perasaan, persepsi, makna, serta pengalaman emosional yang mereka alami. Fenomenologi digunakan untuk memahami esensi pengalaman hidup seseorang melalui deskripsi pengalaman langsung. Teknik. pengumpulan data dilakukan melalui metode Wawancara Mendalam (In-depth Interview). Berdasarkan hasil penelitian dan pembahasan mengenai pengalaman mahasiswa Universitas PGRI Semarang dalam menikmati es kopi kekinian, dapat disimpulkan bahwa aktivitas ngopi memiliki makna yang lebih luas daripada sekadar mengonsumsi minuman. Pengalaman mahasiswa dalam menikmati es kopi kekinian terbentuk dari tiga aspek utama, yaitu pengalaman sensorik, emosional, dan sosial. Dari aspek sensorik, mahasiswa menilai rasa, aroma, dan kualitas kopi sebagai faktor penting dalam menentukan kepuasan. Dari aspek emosional, es kopi kekinian memberikan rasa nyaman, rileks, serta membantu mengurangi stres akibat tekanan akademik. Sementara itu, dari aspek sosial, aktivitas ngopi menjadi sarana untuk bersosialisasi, berdiskusi, dan mempererat hubungan pertemanan. Selain itu, media sosial memiliki peran dalam mengenalkan tren dan kedai kopi baru, meskipun mahasiswa tetap mempertimbangkan kenyamanan dan preferensi pribadi dalam menentukan pilihan. Secara keseluruhan, es kopi kekinian dimaknai sebagai bagian dari gaya hidup mahasiswa UPGRIS yang berkaitan dengan identitas diri, kenyamanan, dan kebersamaan.